Card Macth Circle: Innovative Learning Media on Social Science Learning in Grade IV Elementary School - Sexcio, Exky Bima; Dafit, Febrina (Journal of Education Technology, 2022)
Card Match Circle learning media is a learning media that is used to improve innovative and creative learning outcomes. This media is used because of the lack of availability of innovative learning media in elementary schools. This study aimed to develop learning media products in the form of picture cards in social studies learning in fourth-grade elementary school. This research design uses the ADDIE method, which only reaches the Implementation stage because the researchers only develop and carry out practicality tests. Sources of data in this study amounted to 15 people consisting of 4 experts, 1 teacher and 10 students. The data collection technique consisted of two data collections: the teacher's response, the student's response, the two validation sheets of linguists, media experts, and material experts. The research instrument used was in the form of a linguist validation questionnaire, a media expert validation questionnaire, a material expert validation questionnaire, a student response questionnaire, and a teacher response questionnaire. The data analysis technique is descriptive qualitative and descriptive quantitative data. Based on the data obtained from research from media experts, a total of 100%, material experts in total 100%, and linguists on average 65% and the overall result is an average value of 88%, and it can be concluded that the Card Match Circle media is very valid to be used as instructional media. The analysis results of teacher responses are a total average of 100%, and students are an average of 97% in total, and the overall results are an average of 98%. It can be concluded that the Card Match Circle learning media impacts student learning outcomes. With this media, it can facilitate students in learning. In addition, it makes learning not boring so that students are enthusiastic in following the lessons given by the teacher.